Posture Adopted In Home and Farm Activities by Women of Hilly Terrain - Saikia, R. (Indian Journal of Hill Farming, 2018)
The study was carried out among women of Karbi Hill Tribe residing in Lumbajong Development Block of Karbi Anglong District of Assam. It was observed that sitting on feet is the most common posture among adopted by the women while doing the kitchen related activities, mud plastering and washing of clothes. Sitting on feet, stooping and bending are found to be the common postures adopted by the women while doing the agricultural activities. Among all the postures adopted while doing the home, farm and allied activities most strenuous is sitting on feet. Findings also revealed that pain in waist is more among the women.